Performance Evaluation Indexes in Public Administration Some issues of their actual usefulness - Laura Tampieri (Central European Public Administration Review)
The paper examines the approach to usefulness of performance indicator systems in Public Administration (PA). There are many international studies about this subject, especially from the point of view of efficiency, effectiveness and adequacy. The used approach considers the difference among these indicators based on the level of difficulty in PA implementation. The research compares some indicator systems in European Public Administration considering their easiness and feasibility to apply and connecting these qualities to the basic structures of efficiency, effectiveness and adequacy. The paper aims to compare performance indicator systems of Austria, Italy and Slovenia, emphasizing the relationship between the indicators and their diffusion in government managerial control. In particular the paper underlines the connection between the difficulty of indexes application and the level of diffusion. in Public Administrations.